Pengaruh Reward dan Gaya Mengajar Terhadap Prestasi Belajar IPS di SD Negeri 2 Wonco - Hartinawanti Hartinawanti; Abdul Rahman (STKIP Andi Matappa Pangkep, 2021)
This study aims to determine (i) the effect of rewards on social studies learning achievement; (ii) the effect of teaching style on social studies learning achievement; and (iii) the effect of reward and teaching style simultaneously on social studies learning achievement at SD Negeri 2 Wonco. Methods This research uses the type of ex post facto research. Data collection techniques through questionnaires. The population is all students of SD Negeri 2 Wonco, totaling 136 people for the 2020/2021 academic year. The sampling technique used purposive sampling so that a sample of 45 was determined. The data analysis technique uses prerequisite analysis and inferential analysis. The results of the study show that rewards have a significant effect on social studies learning achievement, this indicates that if the reward is good, the learning achievement of students increases; teaching style has a significant influence on social studies learning achievement, this shows that if the contribution of teaching style is in a good category, the learning achievement of students increases; reward and teaching style simultaneously have a significant effect on social studies learning achievement, this shows that the contribution between reward and teaching style affects the improvement of students' learning achievement.